Characterization, Dissolution, and Solubility of Lead Hydroxypyromorphite [Pb5(PO4)3OH] at 25–45°C - Yinian Zhu; Zongqiang Zhu; Xin Zhao; Yanpeng Liang; Yanhua Huang (Journal of Chemistry)
Dissolution of the hydroxypyromorphite [lead hydroxyapatite, Pb5(PO4)3OH] in HNO3 solution (pH = 2.00), ultrapure water (pH = 5.60), and NaOH solution (pH = 9.00) was experimentally studied at 25°C, 35°C, and 45°C. The XRD, FT-IR, and FE-SEM analyses indicated that the hydroxypyromorphite solids were observed to have indistinguishable change during dissolution. For the hydroxypyromorphite dissolution in aqueous acidic media at initial pH 2.00 and 25°C, the aqueous phosphate concentrations rose quickly and reached the peak values after 1 h dissolution, while the aqueous lead concentrations rose slowly and reached the peak values after 1440 h. The solution Pb/P molar ratio increased constantly from 1.10 to 1.65 near the stoichiometric ratio of 1.67 to 209.85~597.72 and then decreased to 74.76~237.26 for the dissolution at initial pH 2.00 and 25°C~45°C. The average Ksp values for Pb5(PO4)3OH were determined to be 10−80.77 (10−80.57−10−80.96) at 25°C, 10−80.65 (10−80.38−10−80.99) at 35°C, and 10−79.96 (10−79.38−10−80.71) at 45°C. From the obtained solubility data for the dissolution at initial pH 2.00 and 25°C, the Gibbs free energy of formation [ΔGfo] for Pb5(PO4)3OH was calculated to be −3796.71 kJ/mol (−3795.55~−3797.78 kJ/mol).